SAFETY OF CELL-DERIVED SUBUNIT ADJUVANTED INFLUENZA VACCINE FOR CHILDREN VACCINATION: DOUBLE-BLIND RANDOMIZED CLINICAL TRIAL - S.M. Kharit; M.K. Erofeeva; N.Yu. Nikanorov; V.V. Romanenko; S.V. Komleva ("Paediatrician" Publishers LLC, 2010)
This article presents the safety data for cell-derived inactivated subunit adjuvanted influenza vaccine «Grippol Neo» in children 3-17 years old in comparison with reference egg-derived inactivated subunit vaccine «Grippol plus». Good test vaccine tolerability and high efficacy profile is demonstrated. Based on the results obtained vaccine «Grippol Neo» is recommended for mass influenza prophylaxis in pediatry, including National Immunization Schedule.Key words: children, influenza, vaccination, «Grippol Neo».(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):44-49)